Biohydrogen production from brewery effluent in a batch and continuous reactor with anaerobic mixed microbial consortia. Issue 6 (2nd November 2017) - Vijaya Krishna, S.; Kiran Kumar, P.; Chaitanya, N.; Bhagawan, D.; Himabindu, V.; Lakshmi Narasu, M.
ABSTRACT: The biological method of dark fermentative hydrogen production may be a promising cost-effective way of producing biogas for future generations. Dark fermentation has become popular due to its cost-efficient and eco-friendly biological method for hydrogen production. In the present study the feasibility of operational conditions such as pH (4.5–7.0) and temperature (30–60 °C) with different time intervals (0–36 h) from brewery effluent as substrate and anaerobic sludge as inocula under dark fermentation for hydrogen production was studied in batch and continuous mode. The maximum hydrogen yield obtained was observed to be 88% and 49% in batch and continuous modes process respectively.